A national health service : draft memorandum on the government's proposals
1944-04-14 1944 1940s 14 pages - 8 - (2) It is essential that an atmosphere should be created in which the voluntary hospitals may continue regularly to secure voluntary support. (3) Under the scheme all payments from public funds to voluntary hospitals should be made centrally. (4) All capital monies required by hospitals for rebuilding and extension purposes under approved area plans should be made available from central funds to voluntary hospitals on the same terms and conditions as may be available at any time to local authorities. (5) The patient must have freedom of choice of hospital, subject only to the availability and adequacy of the service at the hospital selected. (6) These conditions are the minima that will secure the freedom of voluntary hospitals from domination by the local authorities and must be regarded as conditions precedent to the participation of the voluntary hospitals in the scheme. 12, Grosvenor Crescent, London, S.W.1. 14th April, 1944. 292/847/2/33